Biomimetic nanoparticles delivered hedgehog pathway inhibitor to modify tumour microenvironment and improved chemotherapy for pancreatic carcinoma. (31st October 2018) - Jiang, Ting; Zhang, Bo; Zhang, Long; Wu, Xuemei; Li, Haichun; Shen, Shun; Luo, Zimiao; Liu, Xianping; Hu, Yu; Pang, Zhiqing; Jiang, Xinguo
Abstract: The unique tumour microenvironment (TM) of pancreatic ductal adenocarcinoma (PDA) including highly desmoplastic ECM and low tumour perfusion supports a considerable barrier for effective delivery of nanomedicines. Effectively modulating PDA microenvironment to enhance tumour drug delivery represents a pinpoint in the field of PDA treatment. In this study, it was the first time that biomimetic nanoparticles, which were designed in the form of erythrocyte membrane-camouflaged PLGA nanoparticles (MNP), were utilized for PDA microenvironment modulation. Cyclopamine (CYC), an inhibitor of Hedgehog pathway that contributed a lot to desmoplastic ECM of PDA, was selected as the model drug and successfully encapsulated into MNP. Advantages of CYC-loaded MNP (CMNP) included favourable biocompatibility, long circulation time, and powerful TM modulation effect. CMNP could effectively deliver CYC to the tumour site, disrupt tumour ECM, increase functional vessels, and improve tumour perfusion significantly. The combination treatment with CMNP and PTX-loaded MNP (PMNP) successfully improved PTX delivery to tumour, resulting in remarkable tumour growth inhibition in vivo . Therefore, biomimetic nanoparticles provide a new strategy for modulating PDA TM and will have great potential to improve the therapeutic effects of nanomedicines for PDA patients.